COMPARATIVE STUDY OF GOLD, STOCK AND DOLLAR VALUES AGAINST FLUCTUATION IN RUPIAH VALUE - B1011131018, Herdiastu Yamani Saptania (Jurnal Pembangunan dan Pemerataan, 2017)
The uncertainty of the condition of the world economy is currently making the community needs to know for certain investment instruments to suit the needs of that is stable, secure and can also be used to speculate. This is very useful in ensuring financial life in the future. This uncertainty can be either in the above-mentioned United States Central Bank interest rates that could affect interest rates on Bank Indonesia and political crises that impact to the economy of Indonesia.This research aims to knowingand analyze the development of thegold, stocks and the dollar value of the fluctuations in the rupiah and analyzing variables of a more stable and secure between gold, stocks and the dollar on Indonesia. Types of data used in this study uses secondary data which consists of data for time (time series) 2000-2016. Methods of documentation and models in this study i.e., the calculation of the coefficient of variation.Results from the documentation that researchers have acquired that of the three variables, namely gold, stocks and the dollar, there is a difference of a motif in gold buy it as a precaution because the price is stable, stocks as a means to speculate because it aims to obtain an advantage, and the dollar as a tool to Transact due in international trade are still using the dollar for import and export. Calculation of the coefficient of variation through get results that the value of the dollar which has the most variation is small it is shown that the price of the dollar which has no big price development compared to gold and stocks. This is due to the growing demand for the dollar and a lack of demand for the value of the rupiah, causing the value of the dollar strengthened.Â Keywords: Gold stock fluctuations, fluctuations, fluctuation of the dollarÂ